2013
DOI: 10.4081/jlimnol.2013.s2.e7
|View full text |Cite
|
Sign up to set email alerts
|

Cladocera (Crustacea: Branchiopoda) of South East Asia: history of exploration, taxon richness and notes on zoogeography

Abstract: The history of Cladocera studies in South-East Asia is reviewed, beginning from the early start of explorations in the end of the 19 th century by J. Richard and T. Stingelin. In the first half of the 20 th century, extensive research was carried out by V. Brehm, who investigated material collected by the Wallacea-Expedition and the Deutschen Limnologischen Sunda-Expedition. Later, in the 1970-1980s, C.H. Fernando and collaborators, besides a few other researchers, provided a new series of regional studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 72 publications
(45 reference statements)
1
61
0
2
Order By: Relevance
“…The three species that we identified here (D. dubium, D. excisum and D. sarsi) were expected in this country, as they are very characteristic of the SE Asian plankton (Korovchinsky, 2004(Korovchinsky, , 2013a(Korovchinsky, , 2013b). There were a few cases where we could not determine the exact species, because there were only a few juveniles in the sample.…”
Section: Order Ctenopoda Sars 1865mentioning
confidence: 99%
See 1 more Smart Citation
“…The three species that we identified here (D. dubium, D. excisum and D. sarsi) were expected in this country, as they are very characteristic of the SE Asian plankton (Korovchinsky, 2004(Korovchinsky, , 2013a(Korovchinsky, , 2013b). There were a few cases where we could not determine the exact species, because there were only a few juveniles in the sample.…”
Section: Order Ctenopoda Sars 1865mentioning
confidence: 99%
“…There were only a few publications concerning the Cladocera fauna of other countries (Tanaka and Ohtaka, 2010), sometimes outdated (Shirota, 1966;Thanh et al, 1980). Korovchinsky (2013a) summarised the available information on the SE Asian cladocerans and concluded that among 297 formal species recorded from SE Asia, only 67 species could be regarded as good, while others are junior synonyms or taxa with unclear or/and unconfirmed status in SE Asia. We believe that the present volume (the FISA Proceedings), will significantly contribute to our knowledge on the SE Asian cladocerans, including new Cladocera (Crustacea: Branchiopoda) of Vientiane province and municipality, Laos Korovchinsky (2013a) on the Cladocera of complete SE Asia, by Sinev and Korovchinsky (2013) about Vietnam, and by and about new paludal chydorids of South Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Several taxonomic groups were revised, and several new species were described Sanoamuang, 2008a, 2008b;Korovchinsky, 2011;Sanoamuang, 2004a, 2004b;Sinev, 2011Sinev, , 2012Sanoamuang, 2007, 2011;Sinev and Kotov, 2012;Van Damme and Sinev, 2013;. At present, the cladoceran fauna of Thailand has proved to be considerably better studied than in any other country of the region -Vietnam, Malaysia, Laos, and Сambodia, while Myanmar still remain especially poorly explored (Korovchinsky, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies provide a firm basis within each group for researchers to build on, and in several countries taxonomical efforts spur limnological research. For example, with Korovchinsky (2013) and Rogers et al (2013), we now have a complete overview of all crustacean branchiopods known in literature to date in SE Asia and an idea of what needs to be done, and the same can be said for the freshwater sponges (Manconi et al, 2013) and cave faunas . Alekseev et al (2013) provide a key for Eucyclops in SE Asia, and Van and Van Damme and Sinev (2013) provide new worldwide keys for several cladoceran genera.…”
Section: The Freshwater Invertebrates Of Southeast Asia Volumementioning
confidence: 99%
“…In most cases we lack the basic knowledge on their diversity, geographic distribution and biology. In the waterfleas (Crustacea: Cladocera) for instance, more than 75% of the species recorded from SE Asia need taxonomic revision (Korovchinsky, 2013). Well-equipped natural history museums with representative zoological collections, the basis of biodiversity studies, are still rare in SE Asia, which makes research on the SE Asian freshwater fauna hard for local specialists.…”
Section: Introduction To the Proceedingsmentioning
confidence: 99%